Grapevine Leaf Application of Steinernema yirgalemense to Control Planococcus ficus in Semi-field Conditions - Platt, T.; Stokwe, N.F; Malan, A.P. (South African Journal of Enology and Viticulture, 2018)
The vine mealybug, Planococcus ficus Signoret (Hemiptera: Pseudococcidae), is a key insect pest of South African grapevine. The ability of mealybugs to avoid or resist the action of chemical pesticides has led to the investigation of alternative control methods, such as the application of entomopathogenic nematodes (EPNs). However, EPN application faces challenges, due to the maladaptation of EPN species to aboveground conditions. In this study, the ability of adjuvants to improve the control of P. ficus in grapevine using an indigenous nematode species, Steinernema yirgalemense, was investigated. A trial was performed to assess EPN survival on grapevine foliage, when applied in the morning (high humidity / low temperature) compared with in the afternoon (high temperature / low humidity). In a semi-field trial, the combination of adjuvants Zeba® and Nu-Film-P® resulted in 66% control of P. ficus after 48 h, compared to the use of Zeba® alone (43%), and EPNs alone (28%). Additionally, lower concentrations of EPNs showed predictably lower mortality rates of P. ficus. Significantly, higher EPN survival was recorded at each time interval in the morning, compared with the corresponding interval in the afternoon. This study demonstrates the ability of S. yirgalemense, when applied with adjuvants and at an appropriate time of day, to control P. ficus on grapevine, under semi-field conditions.